Rethinking back-translation for the cross-cultual adaptation of health-related questionnaires: expert translators make back-translation unnecessary - Coulthard, Robert James (2013)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Estudos da Tradução, Florianópolis, 2013.